(untitled) (Fiep Bulletin - online, 2011)
Hemophilia is a hereditary disease, hemorrhagic, predominantly, due the quantitative to deficiencies in the biosynthesis of factors or clotting proteins, or molecular defects (qualitative deficiencies of factors VIII and IX). This study aimed to characterize the scientific literature on quality of life of hemophiliacs in the databases of the BVS / BIREME (LILACS, MEDLINE, SCIELO, ADOLEC and MEDCARIB) according as the year of publication (2003 to April 2009), type of study and approach, form of publication (abstract and complete), linked to thematic categories, language (English, Portuguese and Spanish) and country of publication. The research is exploratory and descriptive study with prospective data and quantitative approach, carried out in electronic databases available in the BVS / BIREME. Data collection was performed in May/2009, with the use of descriptors "hemophilia" and "quality of life". During the collection, there were found 74 articles: 01 in LILACS, 72 in MEDLINE and ADOLEC in 1. In SCIELO and MEDCARIB no articles were found. Most of the articles surveyed used the descriptive study (37.8%), with a quantitative approach (55.4%), published in an abstract form (95.9%) in the years 2008 (27.0%) and 2004 (19.0%), in english (97.3%) developed in England (68.9%) and USA (14.9%) about psychological adaptation in relation to quality of life in hemophilic patients (31 , 1%), various treatments (20.3%). To avoid psychological problems and improve quality of life is necessary that the patients and their families receive more information about the disease as well as the population and health professionals. Through national campaigns can improve the quality of medical services and encourage patient adherence to treatment.